CHALLENGES IN MANAGEMENT OF ENDOGENOUS ENDOPHTHALMITIS IN CHILDREN: A CASE SERIES - Eko Parulian; Lukman Edwar (Majalah Oftalmologi Indonesia, 2023)
Introduction: Endophthalmitis is one of the most feared disease in ophthalmology because it can lead to loss of vision and loss of the eyeball. Endophthalmitis from endogenous cause are very rarely found in young patients without immunocompromised condition, making it difficult to be diagnosed.  The lack of established guidelines for treating endogenous endophthalmitis also presents challenges for ophthalmologist.  In this case series, we present our management of two pediatric patients with different presentations of endogenous endophthalmitis. We manage to salvage both of the patient’s eye ball with two different approaches. Case Report: Our first patient was a 2-years-old boy with a chief complaint red eye since 10 days before admission. He was previously diagnosed with conjunctivitis. On admission the left eye was not very inflamed but we found hypopion and vitreous haze  from ultrasound, suggestive of endophthalmitis.  We gave the patient systemic antibiotics and did irrigation/aspiration of the anterior chamber. He responded well to our therapy and was discharged on tenth day of admission. 2. A 6-years-old girl with a chief complaint red painful eye since 2 days before admission.  On admission, the eye was very inflamed with limited movement. The USG revealed vitreous haze suggestive of endophthalmitis. She was then given systemic and intravitreal antibiotics but showed poor response. Intravenous steroid was then given and the condition was improved. She was discharged on the fifth day. Discussion: Our two patients came with two different presentations and responds to systemic antibiotics which was considered the mainstay of treatment in endogenous endophthalmitis. The first patient responded well with systemic and intracameral antibiotics while the second patient condition was improved only after the addition of intravenous steroid. Close observation with re-examination and re-evaluation should be done repeatedly to decide which treatment option should be administered. Conclusion: Diagnosis and management of young patient with endogenous endophthalmitis is challenging. Thorough history taking, physical examination, laboratory examination, and microbiology examination should be done to make a prompt diagnosis and management.